2007
DOI: 10.1590/s0101-82052007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of a coupled thermally dependent viscosity flow problem

Abstract: Abstract. In this work, a stationary Stokes flow with thermal effects is studied both mathematically and numerically. First, existence, uniqueness and regularity of the weak solution of the problem are established. Next, fi nite element approximation to the problem, based on a fi xed point algorithm, is proposed. Then, an error estimate between continuous solution and discrete one is obtained. Finally, some numerical tests are presented to confi rm the theoretical results.Mathematical subject classification: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similarly to our former studies [9,17,18], we first establish existence, uniqueness, and regularity of the weak solution of problem (1.2). We apply a fixed point algorithm to the nonlinear coupled problem and then propose a finite element approximation to the iterative solution.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Similarly to our former studies [9,17,18], we first establish existence, uniqueness, and regularity of the weak solution of problem (1.2). We apply a fixed point algorithm to the nonlinear coupled problem and then propose a finite element approximation to the iterative solution.…”
Section: Introductionmentioning
confidence: 90%
“…The existence study for the system of equations can be found in, e.g. [3,[5][6][7], and [2,8,9] for non-Newtonian flows with viscous heating. As our knowledge, there is no mathematical analysis (such as uniqueness and regularity) and numerical analysis for problem (1.2) up to now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation